The effects of activated virgin coconut oil (AVCO) and virgin coconut oil (VCO) on cell membrane of Candida albicans - Nor Izzah binti Mukhtar
Virgin coconut oil (VCO) has been used in treating infections for ages. VCO can be used in preventing and protecting human body from microbial and fungal infections which can cause disease such as oral candidiasis. Oral candidiasis is an infection which is caused by the overgrowth of Candida albicans. However, the knowledge on the mechanism of action of AVCO and VCO on the cell membrane of C. albicans is limited. The aim of this study is to investigate the effects of activated virgin coconut oil (AVCO) and the crude extract of VCO on the cell membrane lysis and the components of cytoplasmic contents of Candida albicans. The differences of fatty acids composition in AVCO and VCO was analysed by using gas chromatography-mass spectrometry (GC-MS) method. To elucidate the effects of AVCO and VCO, live/dead bacterial viability kit was used to investigate the cell viability of Candida albicans in vitro cultures and was observed under fluorescence microscopy. Transmission electron microscopy was used to examine the cellular morphology of Candida albicans after being treated with AVCO and VCO. The cellular leakage of Candida albicans was detected by using UV/Vis spectrophotometer. Cytoplasmic leakage confirms creation of holes in the membrane by AVCO. Disturbance of cell membrane causes pore through which cellular materials (protein and DNA) leakage takes place. AVCO has been proven to have an antifungal effect on Candida albicans by altering the cell walls, disintegrating fungal cell membranes. The results of this study suggested that AVCO may disrupt the structure of the cell membrane and causes the release of cytoplasmic materials of Candida albicans due to the destruction of membrane network. Nevertheless, VCO has shown limited or no antifungal activity on the cell membrane of C. albicans. The study of cellular leakage of cell membrane components of Candida albicans may help to understand the mechanism of action of AVCO which has the potential to be a new antifungal treatment in treating oral candidiasis that can be an alternative to combat this pathogenic fungus which increases its resistance against current antifungal agents. In conclusion, this study proposes that AVCO has higher antifungal activity against Candida albicans compared to the crude extract of VCO.